Aqueous Co‐Solvent in Zwitterionic‐based Protic Ionic Liquids as Electrolytes in 2.0 V Supercapacitors. Issue 22 (1st October 2020) - Lu, Xuejun; Vicent‐Luna, José Manuel; Calero, Sofia; Roldán‐Ruiz, María J.; Jiménez, Ricardo; Ferrer, M. Luisa; Gutiérrez, María C.; del Monte, Francisco
Abstract: High‐performance energy‐storage devices are receiving great interest in sustainable terms as a required complement to renewable energy sources to level out the imbalances between supply and demand. Besides electrode optimization, a primary objective is also the judicious design of high‐performance electrolytes combining novel ionic liquids (ILs) and mixtures of aqueous solvents capable of offering "à la carte" properties. Herein, it is described the stoichiometric addition of a zwitterion such as betaine (BET) to protic ILs (PILs) such as those formed between methane sulfonic acid (MSAH) or p ‐toluenesulfonic acid (PTSAH) with ethanolamine (EOA). This addition resulted in the formation of zwitterionic‐based PILs (ZPILs) containing the original anion and cation as well as the zwitterion. The ZPILs prepared in this work ([EOAH] + [BET][MSA] − and [EOAH] + [BET][PTSA] − ) were liquid at room temperature even though the original PILs ([EOAH] + [MSA] − and [EOAH] + [PTSA] − ) were not. Moreover, ZPILs exhibited a wide electrochemical stability window, up to 3.7 V vs. Ag wire for [EOAH] + [BET][MSA] − and 4.0 V vs. Ag wire for [EOAH] + [BET][PTSA] − at room temperature, and a high miscibility with both water and aqueous co‐solvent (WcS) mixtures. In particular, "WcS‐in‐ZPIL" mixtures of [EOAH] + [BET][MSA] − in 2 H2 O/ACN/DMSO provided specific capacitances of approximately 83 F g −1 at current densities of 1 A g −1, and capacity retentions of approximately 90 % after 6000 cycles when operating at a voltage of 2.0 V and a current density of 4 A g −1 . Abstract : High‐performance electrolytes : The addition of a zwitterion (e. g., betaine) to regular protic ionic liquids (PILs, like ethanolammonium methyl sulfonate) results in zwitterionic‐based PILs (ZPILs) highly miscible in an aqueous co‐solvent mixture of water, DMSO, and acetonitrile. This aqueous co‐solvent in ZPIL operates at electrochemical stability windows of up to 2 V providing remarkable capacitance, IR drop, and coulombic efficiency.